IMPLEMENTATION OF PANCASILA VALUES THROUGH GOVERNMENT POLICIES IN THE EDUCATION SECTOR IN THE ERA OF THE COVID-19 PANDEMIC - nafa, Nafa (Unmul Civic Education Journal, 2022)
The outbreak of Covid-19 outbreak in Indonesia has prompted the government to issue many new policies related to various areas of people's lives. One of them is a policy in the field of education, namely through the establishment of LFH (Learning from Home) policies for all levels of education. The problem that arises is the demand for changes in student behavior from traditional learning methods to independent learning patterns. The purpose of this study was to find out how students apply Pancasila values ​​in carrying out learning in the Covid-19 Pandemic era in line with government policies. The research was conducted with a quantitative approach, starting with a literature study to find out aspects related to Pancasila values, LFH learning methods, and health policies in the Covid-19 Pandemic era. Based on the results of the literature study, a questionnaire was developed to collect data from students. The online version of the questionnaire is made so that it is easy to fill out by respondents, namely 114 college students. The research findings are interesting to observe, namely, the majority of respondents (56.2%) think that government policies in the field of education in the current Covid-19 Pandemic era have not been carried out effectively. Even (73.6%) of students stated that there was a decrease in learning motivation among students. This finding needs to be immediately anticipated by decision makers in universities considering that the start of the next semester will soon begin. The values ​​of Pancasila that are applied at this time are just and civilized humanity and the unity of Indonesia.